EKSTRAK TERSTANDAR SECARA KIMIA DAUN Brucea javanica Merrill - Marissa Angelina; Abdul Mun'im; M Hanafi (Research Center for Chemistry - LIPI, 2011)
The preparation of Brucea leaves have been done for specific parameters and non specific parameter laboratory worb refers to TheNational Agency of Drug and Food Control Regulation for extract quality control. The result for specific extract parameters were the rendement of extraction is 28%, the values of water- extractive and ethanol-extractive are 11.49% and 9.41%, respectively. The result of determination of the non specific parameters of the extract are; loss on drying is 18.95%, the water content is 15.06%, the total ashes is 16.12%. and the level of ashes not dissolved in acid is 11.14%. The analysis of chemical compound shows that the extract containedflavonoid, tannin, and glycoside. For the quantitative control has been measured the level of totalflavonoid wherethe result is 9.901%Keywords : Preparation, Brucea; Specific parameter, non specificparameter, extract